Leveraging Digital Marketing for Maritime Logistics in Indonesia - Barasa, Larsen; Malau, April Gunawan; Sibarani, Mauritz Halomoan Manontang (Jurnal Abdidas, 2024)
This research explores the utilization of digital marketing and e-commerce platforms for enhancing maritime logistics services in Indonesia. Through qualitative inquiry and descriptive analysis, insights were gleaned from interviews with industry professionals. Key findings highlight the prevalence of social media engagement, widespread adoption of e-commerce platforms, and challenges related to digital literacy and skills development. Benchmarking against international best practices reveals areas of strength and opportunities for improvement. Recommendations include investing in digital skills development, fostering collaboration, embracing technology, prioritizing customer-centricity, and cultivating a culture of continuous improvement. By aligning practices with global standards and leveraging digitalization, Indonesian logistics providers can drive sustainable growth and competitiveness in an increasingly digitalized marketplace